The structure of the complex between the arsenite oxidase from Pseudorhizobium banfieldiae sp. strain NT‐26 and its native electron acceptor cytochrome c552. Issue 4 (30th March 2023) - Poddar, Nilakhi; Santini, Joanne M.; Maher, Megan J.
Abstract : The crystal structure of the electron transfer complex between arsenite oxidase (AioAB) from Pseudorhizobium banfieldiae sp. strain NT‐26 and its native electron acceptor cytochrome c 552 (cyt c 552 ) is presented. Cyt c 552 docks within a cleft at the interface of the AioA and AioB subunits, which allows a close association between redox cofactors.; this close association presumably facilitates fast electron transfer and underpins the ability of this organism to respire in arsenic contaminated environments. Abstract : The arsenite oxidase (AioAB) from Pseudorhizobium banfieldiae sp. strain NT‐26 catalyzes the oxidation of arsenite to arsenate and transfers electrons to its cognate electron acceptor cytochrome c 552 (cyt c 552 ). This activity underpins the ability of this organism to respire using arsenite present in contaminated environments. The crystal structure of the AioAB/cyt c 552 electron transfer complex reveals two A2 B2 /(cyt c 552 )2 assemblies per asymmetric unit. Three of the four cyt c 552 molecules in the asymmetric unit dock to AioAB in a cleft at the interface between the AioA and AioB subunits, with an edge‐to‐edge distance of 7.5 Å between the heme of cyt c 552 and the [2Fe–2S] Rieske cluster in the AioB subunit. The interface between the AioAB and cyt c 552 proteins features electrostatic and nonpolar interactions and is stabilized by two salt bridges. A modest number of hydrogen bonds, salt bridges and relatively small, buried surface areas between protein partners are typical features of transient electron transfer complexes. Interestingly, the fourth cyt c 552 molecule is positioned differently between two AioAB heterodimers, with distances between its heme and the AioAB redox active cofactors that are outside the acceptable range for fast electron transfer. This unique cyt c 552 molecule appears to be positioned to facilitate crystal packing rather than reflecting a functional complex.